PEMBELAJARAN MELALUI BERMAIN DALAM RANGKA PENGEMBANGAN KEMAMPUAN BERBAHASA ANAK DI TK ISLAM AL-AZHAR KOTA JAMBI - Pudjaningsih, Wiwik (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2014)
This article explains result of qualitative research "learning through playing at for inÂ framework of ability expansion is having language child in TK Â Islam Â Al Azhar Â KotaÂ Jambi". Â Result Â of Â the Â research Â is Â description Â of Â the Â learning Â related Â to Â planning,Â execution, Â and Â evaluation. Â Its Â individuality Â including Â (a) Â ability Â expansion Â scope Â isÂ having Â language, Â (b) Â bases Â on Â area, Â and Â (c) Â having Â approach Â tematic. Â LinguisticÂ expansion Â covers Â receives Â language, Â lays Â open Â language, Â and Â letter. Â Learning Â isÂ executed in area "Preparation, Plays Role, Log, Nature Material, Imtag, and ArtisticCreativityâ€. Â Theme exploited as unifier development scopes of chlid. The evaluationÂ is Â observation, Â assignation, Â activity Â short Â exchange, Â anecdot Â record-keeping,Â conversation, document, and description of chlid profile.Keywords: learning through playing, ability is having language child, area